Online Training About Entrepreneurship For Asahan University Students In Pandemic Era - M Umar Maya Putra (Institute of Computer Science (IOCS), 2021)
This research is a concept online training about entrepreneurship for Asahan University students in pandemic era. The research goal is making the creativity for young students for getting the willingness and idea to increase the entrepreneurship ability in pandemic era. The method used is an experimental online learning method in the entrepreneurship material and literature study concept with zoom meeting room Website and Seminar (Webinar). The way to tranfer entrepreneurship knowledge based on journals, books mentioned about the creativity for requiring its quality for economics students and invited entrepreneurship beginner conducted with focus in business feasibility concept of tendency for attracting consumers to for buying interest continuously. From the online presentation of the entrepreneurship to Asahan University Student, there are several points that are asked by audiences about entrepreneurship such as the way to get the entrepreneurship willingness in the Asahan University. From the activity, the government actors must commit the achievement of the results of activities to make the brand new approachment in Asahan Regency